Application of ultrasound in tip location of internal jugular vein with tunnel-cuffed central venous catheter - Jing-bo Shi; Sui-jun Liu; Yu-xing Zhu; Yi Gao (Editorial Department of Journal of Clinical Nephrology, 2024)
ObjectiveTo evaluate the value of ultrasound in tip location of tunnel-cuffed central venous catheter through internal jugular vein.MethodsFrom February 2022 to July 2023, 42 patients of chronic renal failure and uremia were admitted for internal jugular vein tunnel insertion with cuff central venous catheter. They were randomized into two groups of ultrasound and control. Tip of catheter was located by ultrasound during operation in ultrasound group and tip of catheter by chest radiograph in control group. Postoperative chest computed tomography (CT) was performed in both groups to determine the tip of catheter. Demographic data, clinical laboratory tests and intraoperative parameters were recorded for examining the differential accuracy of catheter tip between two methods.ResultsNo significant inter-group differences existed in age, gender, body mass index (BMI), primary disease, history of catheterization or laboratory tests (P>0.05). And significant inter-group differences existed in ectopic rate of catheter tip, puncture time and puncture complications (P<0.05). Ectopic rate of catheter tip was significantly lower in ultrasound group than that in control group [(13.1%, 3/23) vs (47.3%, 9/19)](χ²=4.443, P=0.035). Puncture time was significantly shorter in ultrasound group than that in control group [(5.17±0.83) vs (6.26±0.73) min] (t=-4.44, P=0.01). The complications were significantly fewer in ultrasound group than those in control group [(4.3%, 1/23) vs (36.8%, 7/19)](χ²=5.17, P=0.023).Conclusion Ultrasound can not only guide the puncture of internal jugular vein, but also locate the tip of central venous catheters with a high reference value.